(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Geo-electric evaluations of the subsurface structures of federal University Gusau Campus, Zamfara State, Nigeria were carried out using vertical electrical soundings technique (VES). The area lies within the Pre-Cambian Basement Complex of Northern Nigeria. Thirty-six (36) vertical electrical soundings (VES) along six profiles (A-F) were carried out during the survey. The surveys were carried out on grid 500m by 500m. The data obtained were interpreted using computer based program named Zohdy. The result of the interpreted curves reveals three distinct geo-electric curves types were delineated: K, H and HK-curves with H-type having the most prolific aquifer. The result also shows 3 geo-electric layers which were confirm by some borehole lithology. The aquifers in the study area are likely to be found in the fractured basement layers of western and southeastern parts of the study area. The civil engineering work can be sited mostly in the northern and southwestern parts of the study area which are the region of shallow basement within t=he study areas. Further boreholes in the area should reached an effective depth of 75m to 90m and the borehole be supervised by a certified hydrogeologist for optimum groundwater yields. Pumping test should be carried out in order to ascertain the size and type of submersible pump to install.